Chatbot Artificial Intelligence as Educational Tools in Science and Engineering Education: A Literature Review and Bibliometric Mapping Analysis with Its Advantages and Disadvantages - Al Husaeni, Dwi Fitria; Haristiani, Nuria; Wahyudin, W.; Rasim, R. (Universitas Pendidikan Indonesia (UPI), 2024)
This research was conducted to analyze the application, utilization or use of AI chatbots in the education sector based on several previous studies. Bibliometric analysis is used to identify the current status of research and critical points in bibliometric data mapping can help predict future research trends. Data searches were carried out on the Scopus database with the keywords